2006
DOI: 10.1002/ange.200600756
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Specific Protein Modification through CuI‐Catalyzed 1,2,3‐Triazole Formation and Its Implementation in Protein Microarray Fabrication

Abstract: Gezielt ligiert: Ein Proteinexpressionssystem wurde mit der CuI‐katalysierten Bildung von 1,2,3‐Triazolen kombiniert, um ein Protein an seinem C‐Terminus zu modifizieren. Das immobilisierte Stammprotein lässt sich mit kleinen Molekülen ortsspezifisch ligieren (siehe Bild), wobei die Ligation mit einem Diazido‐Linker zu homodimeren Proteinkonjugaten führt. Durch spezifische kovalente Anbindung an funktionalisierte Oberflächen können außerdem Mikroarrays erzeugt werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 29 publications
(12 reference statements)
0
14
0
3
Order By: Relevance
“…Towards this end, numerous surface “anchoring” methods have been studied in an effort to produce “optimized” surface orientations 1,11,12,1825. In particular, it has been suggested that site-specific immobilization strategies cause the immobilized proteins or peptides to adopt certain preferred orientation, reflected in improved performance and stability of biosensors or biochips 1925.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Towards this end, numerous surface “anchoring” methods have been studied in an effort to produce “optimized” surface orientations 1,11,12,1825. In particular, it has been suggested that site-specific immobilization strategies cause the immobilized proteins or peptides to adopt certain preferred orientation, reflected in improved performance and stability of biosensors or biochips 1925.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been suggested that site-specific immobilization strategies cause the immobilized proteins or peptides to adopt certain preferred orientation, reflected in improved performance and stability of biosensors or biochips 1925. For example, Holland-Nell et al observed a distinct difference in the performance of site-specifically vs. randomly immobilized enzymes (aldo/keto reductase AKR1A1); they found that site-specifically immobilized enzymes show a dramatic increase in activity, and greater long-term stability than randomly immobilized enzymes 20.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Site-specific immobilization and thus control over the orientation of proteins is particularly important because, as opposed to nonspecific adsorption, it generates homogeneous surface coverage and accessibility to the active site of the protein. [2] Consequently, different types of bioorthogonal reactions [3] have been developed to attach proteins site-specifically to surfaces and to control protein patterning. [4] Herein, we report the photochemical coupling of olefins to thiols to generate a stable thioether bond for the covalent surface patterning of proteins and small molecules.…”
mentioning
confidence: 99%
“…2 However, the most commonly used chemistries for peptide or protein immobilization, such as amide-bond formation and reductive amination, involve random covalent-bond formation with multiple reactive amino acids in peptides or proteins, which inevitably has a substantial negative effect on peptide activity and, hence, it is very hard to achieve the reproducibility and sensitivity of activity-based assays. 2,[10][11][12] In addition, when peptides are conjugated on the glass surface, conjugation efficiency is another major concern. 13-17 Thus, given the presence of multiple reactive amino acids in peptide or proteins under physiological conditions, and the current limitations to immobilization efficiency, there is a considerable need for highly selective and efficient orthogonal reactions.…”
Section: Introductionmentioning
confidence: 99%
“…24 However, the use of click chemistry to prepare peptide microarray has not been reported even though click chemistry have been used for other biomolecule conjugation. 11,25,26 The Cu (I) catalyzed 1,3-dipolar cycloaddition of azide and alkyne to form a triazole, the quintessential example of click chemistry, has been established as an important tool for chemical and biological modification of biomolecules. [27][28][29] Click reaction is widely used to conjugate biomolecules because click reaction can rapidly achieve high yields, and more importantly, it is completely compatible with aqueous conditions.…”
Section: Introductionmentioning
confidence: 99%